A 2019 Social Accounting Matrix for Kenya including malaria epidemiological and agroecological zones - Zuhal Elnour Hamad Mohammed; Khalid Siddig; Harald Grethe (Humboldt-Universität zu Berlin, Faculty of Life Sciences, Department of Agricultural Economics, 2022)
This paper documents the development of a 2019 Social Accounting Matrix (SAM) for Kenya. A special feature of this SAM is its spatial disaggregation according to malaria epidemiological and agroecological zones. It is built using data from the Kenya National Bureau of Statistics (e.g., the economic survey 2021 and the 2019 Kenya Population and Housing Census), the Central Bank of Kenya (i.e., the Diaspora Remittances Survey), the Kenya Ministry of Health (i.e., the Kenya Malaria Strategy 2019-2023), the 2019 SAM for Kenya, constructed by Thurlow (2021), and the 2017 Kenyan SAM, developed by Ferrari et al. (2020). Compared to the existing Kenyan SAMs, this SAM has two vital features. First, it includes 30 labour categories, disaggregated by skill levels and malaria epidemiological and agroecological zones. Second, households are classified into 40 representative groups according to residence place, income quantiles, and malaria epidemiological and agroecological zones. Consequently, this SAM is a valuable database for conducting economy-wide analysis of health policies, e.g., assessing the implications of implementing malaria control and elimination strategies or changes in labour availability due to malaria effects on morbidity and mortality.
Keywords: E16; Q53; 330; social accounting matrix; malaria; economic structure; household welfare; human health; public health strategy; policy analysis; Kenya